Factors affecting downy mildew infection of fenugreek - G.S. SAHARAN, SOM PRAKASH and (Indian Phytopathology, 2002)
Temperature regime of 18Â°C gave maximum infection frequency of Peronospora trigonella on fenugreek. The per cent infection differed significantly under dark and light conditions with higher infection points under dark conditions. The inoculum of 12h age caused maximum infection. The conidial inoculum used after washing at 5000 rpm was found more virulent with higher rates of infection. Highest infection occurred at flowering stage followed by pod formation growth stage of the crop. Downy mildew infection was initiated when host leaves were kept wet for 6 h. A leaf wetness period of 12h was found optimum to get maximum infection. There was 100 per cent infection on the host leaves when they were inoculated soon after wiping of their surface.